Effect of Self-Esteem, Emotional Intelligence and Psychological Well-Being on Resilience in Nursing Students - Young Eun Lee; Eunyoung Kim; Sun Young Park (Child Health Nursing Research, 2017)
Purpose: The purpose of this study was to investigate factors affecting resilience in nursing students. Methods: A survey was conducted with 200 nursing students at a college and a university in P city and K city. Data were collected from March 1 to 20, 2017, and analyzed with SPSS PASW 22.0. Results: In the hierarchical analysis, factors affecting resilience were emotional intelligence (β=.39, p<.001), psychological well-being (β=.31, p<.001), and self-esteem (β=.16, p=.010). The variable that had the highest impact was emotional intelligence and the explanation power of the regression model was 65%(F=34.40 p<.001). Conclusion: The findings of this study indicate that emotional intelligence, psychological well-being, and self-esteem are essential for resilience in nursing students. Thus, enhancing emotional intelligence and psychological well-being would be an effective strategy to improve resilience in nursing students.